RESISTANCE OF BAMBOO WOVEN CRAFTSWOMEN TO NATURAL EXPLOITATION - Ratna Kumalasari; Sri Kusumo Habsari; Prasetyo Adi Wisnu Wibowo (Universitas Islam Negeri Imam Bonjol Padang, 2021)
The exploitation that occurs in nature is a form of domination that is considered to have a relationship with the dominance that occurs in women because the exploitation of nature goes hand in hand with the oppression of women. Nature causes more and more damage, and women get the impact of that damage that leads them to fight against fundamental issues related to their survival. This paper raises the issue of environmental degradation experienced by women bamboo weaving and their active involvement in maintaining natural resources that act as their source of life. This research is a qualitative research conducted in Cimahpar Village, Girijaya Cianjur, West Java, with data obtained from observations, FGDs, and interviews. The data is focused on the perspective of eco-feminism, namely by examining more deeply the dominance experienced by women who are bamboo craft weaver and their efforts to prevent environmental damage and loss for their living. The results show that woman bamboo craft weavers are aware of protecting their environment, which is manifested by fighting against the attempts to destroy the bamboo ecosystem, leading to landslides. To maintain the bamboo ecosystem, the women of Cimahpar continue to utilize bamboo for various purposes. Subsequently, they protect their environment for their living